The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12888-018-1736-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations between loneliness and perceived social support and outcomes of mental health problems: a systematic review

Abstract: BackgroundThe adverse effects of loneliness and of poor perceived social support on physical health and mortality are established, but no systematic synthesis is available of their relationship with the outcomes of mental health problems over time. In this systematic review, we aim to examine the evidence on whether loneliness and closely related concepts predict poor outcomes among adults with mental health problems.MethodsWe searched six databases and reference lists for longitudinal quantitative studies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

76
666
6
29

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 913 publications
(777 citation statements)
references
References 80 publications
76
666
6
29
Order By: Relevance
“…The finding coheres with previous studies that reported associations between loneliness, depression, and anxious depression [1, 9, 16-18, 47, 55]. For instance, a systematic review [56] reported association between a high level of loneliness and severe depressive symptoms. The results could suggest the collapse of family or social networks and the traditional family support systems for the elderly in Nigerian communities especially in the rural areas [7].…”
Section: Discussionsupporting
confidence: 91%
“…The finding coheres with previous studies that reported associations between loneliness, depression, and anxious depression [1, 9, 16-18, 47, 55]. For instance, a systematic review [56] reported association between a high level of loneliness and severe depressive symptoms. The results could suggest the collapse of family or social networks and the traditional family support systems for the elderly in Nigerian communities especially in the rural areas [7].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, social support may serve as a method for improving the psychological components of disease management, such as coping, anxiety, and depression. This finding is consistent with previous literature indicating that social support may have stronger relationships with psychological outcomes among healthy and chronic condition populations (Uchino, ; Wang, Mann, Lloyd‐Evans, Ma, & Johnson, ). Therefore, social support interventions can be utilized to address the multiple psychological comorbidities that exist with IBD (Bannaga & Selinger, ; Byrne et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…Adults with depressive episode were around 11 times more likely to feel lonely compared to those with no mental disorder [8]. Greater loneliness was also reported to be associated with more severe depressive symptoms and poorer remission from depression in a systematic review [47]. Masi and colleagues [48] described a regulatory loop model of loneliness, in which people who are lonely tend to have negative and biased social cognitions [49].…”
Section: Discussionmentioning
confidence: 99%